Hubungan Sikap, Pengetahuan, Media Massa, Dan Peran Keluarga Dengan Konsumsi Buah dan Sayur Pada Anak Di Madrasyah Ibtidaiyah Miftah Darussalim Martapura - Oklivia Libri; Pramono Pramono; Ardilla Santi (Jurnal Kesehatan Indonesia, 2017)
Fruit and vegetable consumption in children was still less than WHO recommendation of 400 gram per day. Low fruit and vegetable consumption in children can cause failure in growth, bone growth is inhibited, abnormal bone formation, overweight and obesity in school age children, so that if allowed to continue would increase the risk of cardiovascular disease during adulthood. This study aims to determine the correlation of attitudes, knowledge, the mass media, and family roles with the consumption of fruits and vegetables in children’s Madrasah Ibtidaiyah Miftah Darussalim Martapura. This study used cross sectional design conducted in July 2016 at the Madrasah Ibtidaiyah Miftah Darussalim Martapura. Population in this study were male and female students Madrasah Ibtidaiyah Miftah Darussalim Martapura with a total sample of 35 respondents, the sampling techniques is done by using the techniques of random sampling. Data was collected by using questionnaires filled out by the respondents and interview semi quantitative food frequency quantitative. The results showed that 54% of respondents who eat fruit and vegetables meet the 400 grams per day. Of the results the bivariate using chi-square test there is a significant correlation between attitudes (OR= 8,5: CI= 1,4-49,5), knowledge (OR= 8,5: CI= 1,4-49,5), the mass media (OR= 6,2: CI= 1,3-27,9). The results of multivariate logistic regression test are the most dominant variabel is knowledge, because knowledge has a greater chance than the attitude, the mass media, and family roles of (OR= 25,158).